81 A single centre retrospective study evaluating the discharge process of newly placed feeding tubes from a specialist children's hospital. (23rd February 2023) - Rothman, Brittany; Cheng, Lauren; Fienberg, Julie; O'Connor, Graeme
Abstract : Background: Children who are unable to meet their nutritional requirements orally require feeding tubes to promote growth and development. Hospital discharge describes a point at which inpatient hospital care is completed and care is transferred to the community. This discharge process involves several actions from hospital-based health care professionals, to ensure a patient's transition is safe, efficient and prevents delays. Methods: This study was conducted between March-June 2022 to review the setup process for newly placed feeding tubes for patients discharged from hospital to community settings. Data was extracted using the hospital electronic record to compare against the trust nutrition policy for the following factors: -Ward staff inform dietitians with minimum of five working days' notice. -All progress and planning is fully documented in patient's electronic record. -Patients cannot be discharged from hospital until they have all necessary equipment. Results: This study reviewed thirty-three paediatric discharges over several wards and specialties. Patients were discharged to various community trusts and had different community suppliers compared to that of the hospital. The number of staff members who informed dietitian five days prior to discharge was 55% and 45% of the ward dietitians did not receive minimum notice. Completion of documentation of training and service co-ordination could not be found in 89% of patients' medical records. Only 58% of patients received home equipment and supplies prior to discharge. Of those patients', 15% required changes to their dietetic plans due to a delay in delivery of equipment. Conclusion: This review highlights the disparity in the discharge process for patients with newly placed feeding tubes. This ultimately impacts a patient's length of stay in hospital and shows the need for further ward training to follow trust guidance and ensure collaboration of services before a patient is discharged to the community.